Hukum Pidana Sebagai Last Resort Dalam Undang-Undang Perlindungan Dan Pengelolaan Lingkungan Hidup - Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2020)
This study aims to analyze the theoretical problems in placing criminal law as a last resort only on offenses in Article 100 paragraph (1) of the PPLH Law and the notion is related to the characteristics of environmental offenses. As a normative legal research, this study uses the statutory, the history, and the conceptual approaches. The results of the study concluded that the placement of criminal law as a last resort only in Article 100 paragraph (1) of the PPLH Law is theoretically problematic. The offenses in the Article, as well as the offenses in Article 101, Article 102, Article 103, Article 104, Article 107, and Article 109 (businesses/activities that are mandatory to EIA), meets the criteria for a real danger model (concrete endangerment) which requires direct contact between contaminated material and the environment carried out in an unlawful manner. Criminal law as a last resort should apply to offenses that enter the abstract endangerment model as regulated in Article 109 (businesses/activities related to UPL-UKL), Article 110, and Article 111 because they are purely administrative violations, there is no direct contact between material polluted with the environment, and protect ecological values indirectly through the provision of intervention mechanisms for the government to prevent environmental losses.